2023
DOI: 10.1111/tpj.16086
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific introgression patterns reveal the origins of worldwide cultivated bananas in New Guinea

Abstract: Hybridizations between Musa species and subspecies, enabled by their transport via human migration, were proposed to have played an important role in banana domestication. We exploited sequencing data of 226 Musaceae accessions, including wild and cultivated accessions, to characterize the inter(sub)specific hybridization pattern that gave rise to cultivated bananas. We identified 11 genetic pools that contributed to cultivars, including two contributors of unknown origin. Informative alleles for each of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
66
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(82 citation statements)
references
References 49 publications
14
66
2
Order By: Relevance
“…We also showed that the contribution of M. schizocarpa , previously thought to be restricted to a few M. schizocarpa × M. acuminate cultivars and suspected to be present in east African highland bananas, was present in Plantain and Silk. It is worth noting that there is a significant difference between the Silk reported in (Martin et al, 2023) and ours, so we speculate that they may not be the same Silk cultivar.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…We also showed that the contribution of M. schizocarpa , previously thought to be restricted to a few M. schizocarpa × M. acuminate cultivars and suspected to be present in east African highland bananas, was present in Plantain and Silk. It is worth noting that there is a significant difference between the Silk reported in (Martin et al, 2023) and ours, so we speculate that they may not be the same Silk cultivar.…”
Section: Discussioncontrasting
confidence: 50%
“…Secondly, in order to reduce false positives, the SNPs results were adjusted with the collinear block (1 kb, 10 kb and 20 kb) of the genomes. Thirdly, the results were compared with those of previous studies (accession numbers: Plantain 148 and 149, Silk 139 and 140) (Martin et al, 2023). Combining the above steps, the final results were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…zebrina (A) [2,3]. However, sequencing data showed that the AAA-EA has large introgressions from another wild species, M. schizocarpa [4]. These bananas (Musa spp.)…”
Section: Introductionmentioning
confidence: 99%